PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER UNTUK SISWA KELAS X SMK SEMESTER GANJIL PADA MATA PELAJARAN INSTALASI LISTRIK DASAR - Dendy Dewa Widjaya Putra; Syaad Patmanthara (SENTIA 2016, 2016)
Learning activities problems occur at SMK PGRI 3 Malang are less-interested students in Basic Electricity Installation, caused the teacher in the learning process is still using textbooks and media powerpint form. From these problems, the researcher develop computer assisted learning media of Basic Electrical Installation Subject. The results of this product is CD (Compact Disk) form. The purpose of this product is: (1) To create computer assisted learning media of basic electricity installation subject for SMK; (2) Developing computer assisted learning media of basic electricity installation subject for SMK; (3) Testing the computer assisted learning media properness of basic electricity installation subject for SMK. The research model used in development is a Borg & Gall model. Validation is validated by some experts, that are: (1) The product validated by expert media reached 91.25%; (2) Material expert reached 89.70% (3) Testing results by the teachers reached 98.53%;(4) Testing results by student reached 92.50%. Based on the results of the validation, it can be concluded that the Computer Assisted Learning Media of Basic Electricity Installation Subject is properly to be used in the learning activities at SMK PGRI 3 Malang, especially in Basic Electricity Installation Subject.